Detection of acquired resistance genes for vancomycin in local isolates Escherichia coli and its relationship with other resistance models - Shahad Hisham Mahmood; Ahmed Mohamed Turkey; Ilham Abdulhadi Khalaf (مجلة جامعة الانبار للعلوم الصرفة, 2018)
This study included the collection of 374 samples (distributed according to the source of collection ) as clinical samples (urine, wounds, burns, feces) from Ibn – Al – Baladi childbirth Hospital, AL- Yarmouk Teaching Hospital and Imam Ali Hospital in Baghdad, from both genders of different ages. As well as environmental samples (Tigris river water in Baghdad and soil samples) were collected from Baghdad region at the same period. The bacterial isolation and identification were conducted on a total of 77 isolates of Escherichia coli (20.58%) after their testing on culture media , microscopic examination with the biochemical tests by using Api – 20 E and VITEK2. The results of sensitivity test against vancomycin showed that 73 isolates of Escherichia coli resistant (94.18%) and 4 isolates with intermediate resistance (5.19%) were performed on Muller-Hanton agar using disk diffusion method . Chromosomal and plasmid DNA were extracted for 31 isolates in a molecular techniques for precise identification. Molecular detection was achieved for all isolates ( of various pathogens ) by using a specific 16SrRNA gene . Owing to the resistance and sensitivity results obtained with the method diagnosis,29 clinical and 2 environmental samples were selected for detection and molecular study . This molecular study detected the vancomycin resistance genes of Enterobacteriaceae in Iraq for the first time . Both chromosomal and plasmid DNA were used in PCR technique to diagnose the Vancomycin resistance genes by using specific primers (VanA,VanB,VanC) . Results of the electrophoresis on agarose gel cleared that all isolated Escherichia coli possessed resistance gene on their plasmid DNA or chromosomal DNA or on both of them with variable ratios .